A microarray analysis highlights the role of tetrapyrrole pathways in grapevine responses to "stolbur" phytoplasma, phloem virus infections and recovered status. (January 2016) - Punelli, Federico; Al Hassan, Mohamad; Fileccia, Veronica; Uva, Paolo; Pasquini, Graziella; Martinelli, Federico
Abstract: After providing a picture of the global transcriptomic changes of grapevine responses to "stolbur" phytoplasma, the recovery status and molecular responses to the phytoplasma and virus co-presence were analyzed. NimbleGen ® Vitis vinifera genome arrays were used. Lower transcript abundance of the genes involved in photosynthesis, trehalose, phospholipids was observed in response to the presence of "stolbur" phytoplasma. The expression of the genes involved in tetrapyrrole increased. The recovered plants showed that the transcripts involved in ATP synthesis and amino acid metabolism, secondary metabolism and biotic stress-related pathways increased. Recovery was associated with tetrapyrrole pathway repression. Co-infection with viruses induced the genes involved in the hormone categories (cytokinin, gibberellin, salicylic acid and jasmonates). Highlights: Primary metabolism was repressed in response to phytoplasma Stolbur. Copresence of phytoplasma and viruses alter hormone-mediated innate response. Tetrapyrrole was affected by both phytoplasma and phloem virus infections. Recovery was linked with the induction of ATP synthesis and amino acids. Recovery was associated with tetrapyrrole pathway repression.